Answer: D. (-1 , -1)
Explanation:
The given system of linear equations :
![x + 3y = -4------------(1)\\\\x + 5y = -6---------------(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/3dd6whq6wnlepugxtjo2io4aqfaezta0lw.png)
Subtract equation (1) from equation (2) , we get
![2y= -6-(-4)=-6+4=-2\\ 2y=-2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/br7u7xca97oy98d07zs07u8c1l5nkcdsw9.png)
Divide both the sides by 2 , we get
(3)
Substitute the value of y=-1 in equation (1) , we get
![x + 3(-1) = -4](https://img.qammunity.org/2020/formulas/mathematics/middle-school/pkr5g6vodgya245ifixamfkjs97bflhiak.png)
![x -3 = -4](https://img.qammunity.org/2020/formulas/mathematics/middle-school/68bmc74soxwo2gh3zv3d8w26rileq5yd3k.png)
Add 3 on both sides , we get
(4)
From (3) and (4) , the solution to the given system = (-1 , -1)
Hence, the correct answer = (-1 , -1)